Behind the Rainbow, “Tongqi” Wives of Men Who Have Sex With Men in China: A Systematic Review - Wang, Yuanyuan; Wilson, Amanda; Chen, Runsen; Hu, Zhishan; Peng, Ke; Xu, Shicun (Frontiers in Psychology, 2020)
Background: Due to the restrictions and stigmatization of homosexuality in China, there has emerged the ‘Tongqi’, or the wives of men who have sex with men. There are around 14 million Tongqi wives whose needs for support are often overshadowed. This phenomenon has been largely under researched, this review is the first to address the current data on the Tongqi. The aim of this systematic review is to begin to provide insight into the pre-existing data and the further support that is needed for the wives of MSM. Methods: The researchers searched PubMed, Web of Science, EMBASE, PsycINFO, CNKI, Sinomed and WangFang databases from their inception date until June 7, 2019. Handsearching was also completed to provide a rich data set. Results: The articles were summarized and analyzed for thematic clusters. From the selected article, five themes emerged, including Sexual Health Issues, Intimate Partner Violence, Mental Health Status, Marriage Dissatisfaction, and Coping Strategies. These themes often intersected to provide a complex understanding of the current gaps in support provided to Tongqi. Conclusion: Tongqi wives remain a hidden population in Chinese mainstream society, who deserves a sensitive approach to support. The study revealed that the MSM wives suffer severe mental, physical, health, and life related harms. However, instead of situating them into the victim roles, many women take on an identity of empowerment and are working together, aiming to make social changes. In order to address the Tongqi phenomenon, it is also essential to reduce the discrimination towards homosexuality. Tongqi are a special group of Chinese women, they require further intensive research attention.